The impact of deprivation and neighbourhood food environments on home food environments, parental feeding practices, child eating behaviours, food preferences and BMI: The Family Food Experience Study-London - Andrea D Smith; Alice Kininmonth; Kristiane Tommerup; David Boniface; Chiara Gericke; Tiffany Denning; Carolyn Summerbell; Christina Vogel; Clare Llewellyn (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Childhood obesity inequalities in England persist despite targeted interventions focused on promoting healthy diets and food environments. This study, part of the Family Food Experience Study-London, aimed to investigate the impact of deprivation and neighbourhood food environments on home food environments, parental feeding practices, child eating behaviours, food preferences, and child BMI. Methods Families (n = 728) with primary school-aged children were recruited from four socioeconomically diverse London boroughs in 2022. Data were collected through computer-assisted interviews (30.8% in-person, 69.2% telephone) on home food environment, parental feeding practices, and children’s eating behaviours and food preferences. Deprivation was characterised using a composite measure of family and neighbourhood indicators of socioeconomic position. Neighbourhood food environment exposures were estimated from individualised activity spaces derived from home postcodes and reported commuting patterns. Child BMI was measured objectively. Generalised linear models examined cross-sectional associations between deprivation and neighbourhood food environment with family food-related outcomes, adjusting for school-level clustering, child sex, age and ethnicity. Results Greater family deprivation was significantly associated with more ‘obesogenic’ family food practices, child eating behaviours and child BMI. Deprivation was linked to higher food responsiveness (β = -0.12, p = 0.002), emotional overeating (β = -0.11, p < 0.001), and increased desire to drink (β = -0.26, p < 0.001). Parents in more deprived households used more emotional (β = -0.10, p < 0.05), instrumental (β = -0.11, p = 0.003) and pressuring feeding practices (β = -0.14, p < 0.001). Greater deprivation was also associated with a more obesogenic home food environment (β = -0.19, p < 0.001) and lower meal structure (β = 0.17, p < 0.001). Exposure to less healthy neighbourhood food environments around and between home and school were associated with a more obesogenic home food environment (β = -0.07, p < 0.01), but no significant associations were found with feeding practices, child eating behaviours or child BMI. Conclusions In this study, family deprivation, rather than neighbourhood food environments, was more strongly linked to obesogenic feeding practices, child eating behaviours and child BMI. Policies focusing on improving neighbourhood food environments will likely be most effective if combined with those addressing systemic issues related to deprivation such as welfare policies (e.g. reforms to benefit caps) or targeted subsidies for healthy food. Future research should examine the independent and accumulative impact that environment and household interventions have on childhood obesity inequalities.